2021
DOI: 10.3390/fire4030039
|View full text |Cite
|
Sign up to set email alerts
|

Towards Understanding Fire Causes in Informal Settlements Based on Inhabitant Risk Perception

Abstract: Informal settlements (ISs) are a high-risk environment in which fires are often seen. In 2019 alone, 5544 IS fires were reported in South Africa. One of the main problems, when investigating an IS fire, is determining the fire cause. In the last 15 years, approximately 40% of the fire causes were classified as ‘undetermined’ in South Africa. Furthermore, the cases where the fire causes have been determined, do not provide the necessary information to comprehend why the fire started. This paper seeks to gain be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Informal settlements around Cape Town are also at high risk of destructive, runaway fires (Pharoah, 2014;Kahanji et al, 2019;Flores Quiroz et al, 2021). Although fires have long been a problem in neighbourhoods with inadequate access to formal electrical connections, the increasing frequency of dry conditions and high winds combine to make fire weather more likely and thus fires become both more frequent and potentially more destructive (Williams et al, 2019).…”
Section: Recurrent Shack Fires In Overcome Heightsmentioning
confidence: 99%
“…Informal settlements around Cape Town are also at high risk of destructive, runaway fires (Pharoah, 2014;Kahanji et al, 2019;Flores Quiroz et al, 2021). Although fires have long been a problem in neighbourhoods with inadequate access to formal electrical connections, the increasing frequency of dry conditions and high winds combine to make fire weather more likely and thus fires become both more frequent and potentially more destructive (Williams et al, 2019).…”
Section: Recurrent Shack Fires In Overcome Heightsmentioning
confidence: 99%
“…South African informal settlers perceive open fire cooking and settlement density as the greatest hazard for fire ignitions and irresponsible drinking in IY (Flores Quiroz et al, 2021;Zweig et al, 2018). However, implementing electrical cooking and settlement density reduction requires a multi-stakeholder approach.…”
Section: Figure 5-(x Represents the Mean * P ≤ 005 Between All Groups...mentioning
confidence: 99%
“…Recently, Dupey & Smith (2019) found that a wildfire can trigger residents to participate in risk mitigation behaviours. Flores Quiroz et al (2021) disputed this claim after they investigated fire risk perception in Imizamo Yethu (IY) but focused on what the elements residents believe cause fire in IY, not how they perceive the hazard of fire itself. Few studies have empirical data collected on residents' fire perception before and directly after a fire event.…”
Section: Introductionmentioning
confidence: 99%
“…Informal settlements around Cape Town are also at high risk of destructive, runaway fires (Pharoah, 2014;Olivier and Eksteen, 2017;Walls, Zweig and Pharoah, 2017;Kahanji, Walls and Cicione, 2019;Flores Quiroz, Walls and Cicione, 2021a;Flores Quiroz, Walls and Cicione, 2021b). Although fires have long been a problem in neighbourhoods with inadequate access to formal electrical connections, the increasing frequency of dry conditions and high winds combine to make fire weather more likely and thus fires become both more frequent and potentially more destructive (Williams et al,2019).…”
Section: Recurrent Shack Fires In Overcome Heightsmentioning
confidence: 99%